Effect of Climate Change and Loss of Habitat on Migratory Birds - Mei, Xinyue (Transactions on Environment, Energy and Earth Sciences, 2024)
Climate change and habitat loss have influenced many species of organisms globally. Migratory birds are one of the most responsive animals towards climate change and habitat disruption, many species of migratory birds have a rapid decline in population in recent years because of these two factors. The aim of this article is to conclude information among the data available to achieve a better understanding of the challenges faced by migratory birds under the situation of climate change and suggest ways of preserving these species of migratory birds. This paper is mainly focused on the effects on migratory birds, especially from a perspective of a decline in population, caused by climate change and habitat loss caused by both natural and human factors. Causes such as frequent forest fires and early, warm springs are discussed in this paper. The effect on migratory birds by warm springs is causing a mismatch between food availability and breeding peak, causing inefficient breeding in many species of migratory birds, while the habitat loss caused by increasing forest fires is causing a decline in the population of migratory birds by not only decreasing their efficiency in breeding but also forced them to migrate to a less optimum habitat for reproduction.